Development of Fruit Cultivation and Production in Jordan 1980-2019 - Shatat , Fahmi Abdelfattah (Jordan Journal of Agricultural Sciences, 2021)
Until the end of the seventies of the last century fruit growing in Jordan was mainly concentrated in the Jordan Valley as irrigated fruit culture which mainly included citrus and bananas. In addition, fruit growing existed in the highlands as rainfed fruit culture including main olives, grapes, almonds, plums, figs, and others. While the irrigated agriculture in the high areas was limited to the lands surrounding the valleys that have springs (Wadi Jerash, Wadi Salt, Zarqa Torrent, Wadi al-Rayyan, Wadi Musa, and others), as fruit trees were planted in mixed orchards that include several types such as figs, pomegranates, and berries in relatively small areas. The increase in income accompanied by increased demand for traditional and non-traditional fruits in the early eighties encouraged the private sector to inject large capitals to invest in the cultivation of fruit trees and to desire many vegetable growers to move to the cultivation of fruit trees, which led a major transformation in the area and production of fruit crops. These changes included the types and varieties of fruits and the origins grafted on those varieties, planting densities, tree training and pruning, fruit harvesting, and handling methods. In the olive field new efficient olive pressing facilities were introduced. In the field of irrigation, a transition has been made from traditional irrigation with basins to drip irrigation which helped in saving irrigation water. This transformation uses fertilization by fertilizing with irrigation (Fertigation, which helped in increasing the efficiency of the fertilization operation. Fruit kinds that witnessed a dramatic change in production included peach and nectarine in the Badia region, palms in the Jordan Valley, and apple production in the Shoubak area. Many institutions such as the Ministry of Agriculture, National Center for Agriculture Research and Technology Transfer, Faculties of Agriculture, Jordanian Agriculture Engineers-Trade Union, Jordan Television, and the private sector all contributed to laying the foundation stone for this transformation and its contribution to this day.